Scribal practices and approaches reflected in the texts found in the Judean desert - Tov, Emanuel. (Studies on the Texts of the Desert of Judah, 2004)
This monograph is written in the form of a handbook on the scribal features of the texts found in the Judean Desert (the Dead Sea Scrolls). It deals in detail with the material, shape, and preparation of the scrolls; scribes and scribal activity; scripts, writing conventions, errors and their correction, scribal signs; scribal traditions; differences between different types of scrolls (e.g., biblical and non-biblical scrolls), the possible existence of scribal schools, such as that at Qumran. In most categories, the analysis is meant to be exhaustive. The detailed analysis is accompanied by tens of tables as well as annotated illustrations and charts of scribal signs. The findings have major implications for the study of the scrolls and the understanding of their relationship to scribal traditions in Israel and elsewhere.